2018
DOI: 10.1038/s41467-018-06194-1
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 proteins activate Pseudomonas exotoxins-S and -T by chaperoning a hydrophobic surface

Abstract: Pseudomonas are a common cause of hospital-acquired infections that may be lethal. ADP-ribosyltransferase activities of Pseudomonas exotoxin-S and -T depend on 14-3-3 proteins inside the host cell. By binding in the 14-3-3 phosphopeptide binding groove, an amphipathic C-terminal helix of ExoS and ExoT has been thought to be crucial for their activation. However, crystal structures of the 14-3-3β:ExoS and -ExoT complexes presented here reveal an extensive hydrophobic interface that is sufficient for complex for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Thus, the partner proteins are inactivated either by cofactor capture or by complexation with lysine residues, most likely in the vicinity of the active site, which shows for the III-type lysine residues (Wilch et al, 2017). According to the crystal structure of 14-3-3/ExoS (Ottmann et al, 2007b; Karlberg et al, 2018) and tweezer/K214 (Bier et al, 2013), we can find that the C-terminal of the ExoS is occupied at the same position for tweezer, which further indicates that the 14-3-3/ExoS PPI system could be disrupted by the tweezer molecule and result in the loss of activity of ExoS.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the partner proteins are inactivated either by cofactor capture or by complexation with lysine residues, most likely in the vicinity of the active site, which shows for the III-type lysine residues (Wilch et al, 2017). According to the crystal structure of 14-3-3/ExoS (Ottmann et al, 2007b; Karlberg et al, 2018) and tweezer/K214 (Bier et al, 2013), we can find that the C-terminal of the ExoS is occupied at the same position for tweezer, which further indicates that the 14-3-3/ExoS PPI system could be disrupted by the tweezer molecule and result in the loss of activity of ExoS.…”
Section: Resultsmentioning
confidence: 93%
“…Such kind of structural characteristics have been suggested to be essential for 14-3-3s stability and functional activity, e.g., 14-3-3ζ (Messaritou et al, 2010). When 14-3-3s function as adaptor proteins in the functionally regulation of other proteins, the U-shaped groove serves as the key point via interaction with two motifs on single or multiple client proteins (Alblova et al, 2017; Chalupska et al, 2017; Karlberg et al, 2018). Inhibitors can thus be designed based on the following strategies, e.g., blocking client proteins moving in the binding groove or breaking the dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphopeptide binding in the AGs of 14-3-3 preferentially occurs when the phosphoresidue embedded consensus motifs reside within intrinsically disordered regions (IDRs) of protein partners 17 that contain sufficient flexibility required for binding to a rather rigid 14-3-3 dimer 1822 . Motif I (R[S/F/Y/W]XpSXP), motif II (RX[S/Y/F/W/T/Q/A/D]Xp(S/T)X[P/L/M]) and motif III (pSX 1–2 –COOH), where pS/T is phosphorylated serine or threonine, have been characterised 23,24 , although targets deviating from these canonical motifs have also been reported 25,26 . In line with the disorder-to-order transition (folding) upon binding principles 20,22 , 14-3-3 proteins are thought to significantly restrict the conformational space sampled by the phosphopeptides within the complex, thereby being able to affect partner protein conformation and activity 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Other crystal structures reported recently have been those of yeast 14-3-3 protein Bmh1 complexed with neutral trehalase Nth1 at a 2:1 stoichiometry 42 and of 14-3-3β with non-phosphorylated exotoxins ExoS/ExoT at either 2:1 or 2:2 stoichiometry 25 . These few structures revealed that the secondary interfaces may be important for maintaining the architecture of 14-3-3 complexes, although whether they are sufficiently affine and specific on their own without the phosphopeptide binding remains a question difficult to address.…”
Section: Introductionmentioning
confidence: 99%
“…The PPI of 14-3-3 with the carbohydrate-response elementbinding protein (ChREBP) regulates transcription of glucoseresponsive genes. Whereas most of the 14-3-3 clients require to be phosphorylated prior to 14-3-3 binding 19,20 , ChREBP is one of the very few phosphorylation-independent 14-3-3 partner proteins [21][22][23] and interacts with 14-3-3 in a unique α-helical conformation (residues 117-137) 24 . A free sulfate or phosphate in the 14-3-3 phospho-accepting pocket interacts with both proteins 24 .…”
mentioning
confidence: 99%